Sluggish giants, sticky cultures, and dynamic capability transformation - Majumdar, Sumit K (Journal of Business Venturing, 2000)
Using a theoretical framework derived from contemporary literature this paper investigates whether large and culturally dominant firms can transform their capabilities over time. Strategic capabilities, as articulated in theory, include resource accumulation and resource configuration. To these is added the capability of resource utilization which comes about because of tacit and inimitable intra-firm coordination skills and is a key performance measurement metric. This article evaluates whether large firms in the U.S. telecommunications industry have been able to effect a transformation in their strategic performance over a 16 year period of time: 1975 to 1990. Since the late 1960s and early 1970s many measures have been undertaken to restructure the industry environment, and these culminated in the 1984 divestiture by AT&T of this 22 Bell Operating Companies (BOCs) to seven Regional Holding companies (RHCs). Simultaneously a series of steps opened competition in many markets for not only the RHCs but for the other local operating companies, of which there are approximately 25 large ones, which in many cases are bigger than some of the companies belonging to the RHC fold. The local operating companies have faced a major transformation in their environment in the last 10 years. Once protected monopolies, they now face increasing competition in many market segments, which were once their profit sanctuaries enabling them to cross-subsidize many unprofitable operations. For the larger operating companies once owned by AT&T there was the shock of divestiture and re-birth, providing them an opportunity to engage in entrepreneurially oriented behavior. Thus, the U.S. telecommunications industry provides a useful laboratory within which to analyze performance and capability transformation. Additionally, one of the key issues that the literature is concerned with is the transformation in the performance of existing organizations. This article provides evidence on the key issue of corporate performance transformation for the principal firms that comprise one of the most important industries of contemporary times. It is a transformation that continues at an even faster pace today. The results show that in a dynamic setting size no longer materially influences negative performance. Inertia arguments about the ability of large firms to effect change are not validated in the context of a dynamic U.S. telecommunications industry. With a larger variety and pool of resources available, larger firms can undergo transformation through a process of dynamic learning as effectively as smaller firms. The relative transformation of the erstwhile Bell Operating Companies is a testimony to this assertion. The results have some implications for downsizing. Received wisdom means that less is better and smaller is swifter. Downsizing means dispersal of assets and resources, particularly human resources which embody firm-specific skills and knowledge. Which types of resources are lost in this process is critical to the eventual success of such endeavors. With downsizing, the ability of large firms to transform themselves via internal learning may be lost. Dynamic learning implies information scale economy exploitation, and to the extent that critical mass is reduced through downsizing there is lesser diffusion of information and knowledge. As a qualitatively important part of this human capital mass is reduced, there is less impact of future learning as firm-specific knowledge, which could be combined with emergent information to create new capabilities disappears. In such circumstances whether large firms can transform themselves successfully is a salient issue that ought to be further evaluated.